Analisa Karakteristik dan Kebutuhan Ruang Parkir Masjid Al Alam Kota Kendari - Andi Ahdan Amir; Hasrudin Hasrudin; Made Suda (Universitas Sulawesi Barat, 2022)
The objectives of this study are to analyze the characteristics of existing parking and analyze the need for parking spaces, parking characteristics were obtained at the Al Alam Mosque in Kendari City, namely the highest parking volume of 345 units of motorcycles and 374 units of cars, a motorbike parking capacity of 1394 units and a car of 666 vehicles, with a parking index of 90.82% for motorcycles and 191.74% for cars. Meanwhile, the need for parking space with two methods is obtained in a ratio of 1.5-3.5 parking space units (SRP) / 100 m² of land area, then a minimum of 190.38 SRP for LV 2nd class standards, or equivalent to 2379.75 m². By the method, the largest difference between the arrival and departure of the vehicle is the largest accumulation of a given time, obtained then it takes 1266 out of the 1410 SRP available. Meanwhile, for cars, 1277 SRP from the 666 available SRP or equivalent to 7,637.5 m² are needed.